Semantic Aware Multi-Agent System Advantages - Trajche Manev; Sonja Filiposka (Institute of Advanced Engineering and Science, 2014)
Internet changes the way people communicate with each other and also affects the business flow. Technology changes affect how people live and communicate with each other, but they themselves also transform and become more human like. The agent oriented programming and multi-agent systems are relatively new example technologies that manifest these changes in a multifacet way. The goal of this paper is to explore the possibilities one can obtain by combining multi agent systems with the emerging semantic web technologies. This powerful combination leads towards new types of complex system development. Using a case study example, together with a comparison with the traditional system design approach, the paper also discusess the possibilities of semantic agent platforms and their development and shows how developers can benefit from following the standards to agent development.